Retirement in the Post-Revocation Context at One Canadian University: Experiences of Phasing and Delaying - Quint-Rapoport, Mia Joy (Canadian Journal of Higher Education, 2015)
This research study is a phenomenological exploration of academics from one Canadian university who either are participating in a phased retirement program or have delayed their retirement beyond the normal retirement age of 65. It is based on face-to-face interviews with 24 professors, male and female, between the ages of 55 and 69, from an array of disciplines. The results indicate that teaching may be a primary reason why academics choose to retire, that female academics seem to align their retirement plans with those of their partners, and that academics who postpone their retirement feel as though they possess a significant amount of respect within their fields. Since this research is based upon a small sample, it provides a starting point for future research studies, particularly concerning how gender affects the issue of academic retirement.